Recombinant overexpression of the Escherichia coli acetyl‐CoA carboxylase gene in Synechocystis sp. boosts lipid production. (18th February 2021) - Fathy, Wael; Essawy, Ehab; Tawfik, Eman; Khedr, Mohamed; Abdelhameed, Mohamed S.; Hammouda, Ola; Elsayed, Khaled
Abstract: Microalgae have received continued attention as a potential source for biofuel production. However, the lack of suitable strains that provide a lipid‐rich biomass and tolerate harsh condition inhibits their industrial application. This report describes an effort to transform Synechocystis sp. with genes encoding acetyl‐CoA carboxylase (ACC), a key regulatory enzyme in the lipogenesis pathway, from the white mustard plant ( Sinapis alba ) and the bacterium Escherichia coli DH5α using chitosan nanoparticles. Although a recombinant plasmid encoding S. alba ACC failed to express, successful transformation was achieved with a recombinant plasmid encoding E. coli DH5α ACC. The successful transformant, Synechocystis sp. PAK13, exhibited increased ACC expression compared with its wild‐type parent (11.8 vs. 7.2 ng), which significantly increased its lipid content (by 3.6‐fold). Synechocystis sp. PAK13 also exhibited a significant (20%) reduction in photosynthetic pigments, a 1.52‐fold higher glucose content and a 3.5‐fold lower sucrose content than the wild‐type. In conclusion, this report introduces a useful strategy to overexpress the ACC gene in microalgae, creating strains with improved lipid production that are suited to industrial applications.